1994
DOI: 10.1249/00005768-199401000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiopulmonary responses to forward and backward walking and running

Abstract: Backward running has long been used in sports conditioning programs and has recently been incorporated into rehabilitative setting as a method of increasing quadriceps strength while decreasing the joint compressive forces about the knee. Although backward locomotion has been studied kinetically, the metabolic cost of backward walking or and/or running has not to my knowledge been previously characterized. O 2 consumption and other cardiopulmonary variables were measured under constant speed exercise during ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
102
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 1 publication
13
102
0
2
Order By: Relevance
“…Secondly, backward walking at the higher speeds (1.67 m/sec and 1.91 m/sec) is demanding. Although this study was designed to control for subject fatigue by randomizing the order of speeds, allowing ample recovery between exercise bouts, and limiting the duration of work at each speed to 6 minutes, subjects reported local muscular fatigue and delayed onset muscle soreness, similar to findings reported previously (7,12). In addition, the mean rating of perceived exertion was 13 (somewhat hard) and 15 (hard) at the fastest two speeds.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Secondly, backward walking at the higher speeds (1.67 m/sec and 1.91 m/sec) is demanding. Although this study was designed to control for subject fatigue by randomizing the order of speeds, allowing ample recovery between exercise bouts, and limiting the duration of work at each speed to 6 minutes, subjects reported local muscular fatigue and delayed onset muscle soreness, similar to findings reported previously (7,12). In addition, the mean rating of perceived exertion was 13 (somewhat hard) and 15 (hard) at the fastest two speeds.…”
Section: Resultsmentioning
confidence: 62%
“…Schwane et al (16) suggested that performing a novel task requires greater motor recruitment. Flynn et al (7) suggest that there are underdeveloped neuromotor pathways for backward walking. Both of these factors could lead to an increase in oxygen demand when the task is novel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,18 More recently, investigators have studied the cardiovascular and metabolic costs of BW. 6,8,12,17 Backward walking has been used as component of rehabilitation programs for many lower-extremity injuries and for injury prevention. 11 Flynn and Soutas-Little 14 reported that backward running could decrease patellofemoral joint reaction forces and decrease eccentric loading of the patellar tendon, decreases that may prove beneficial in treating patients with patellofemoral dysfunction.…”
mentioning
confidence: 99%
“…Heart rate (HR) and oxygen consumption (VO 2 ) have been shown to be higher during BW than FW at a 0% treadmill grade, 8,17 and similar relationships have been reported for treadmill grades of 1% and 5%. 6,12 According to the American College of Sports Medicine guidelines, 1 exercise needs to be maintained at an intensity of 50% to 85% maximum oxygen consumption (VO 2max ) or 60% to 90% maximum heart rate (HR max ) to sustain or improve cardiovascular fitness. The ability of BW to achieve these levels of cardiovascular activity at a slower speed and lower grade, as compared to FW, could decrease injury potential for people undergoing rehabilitation of knee injuries.…”
mentioning
confidence: 99%